Service-Oriented Computing 11th International Conference, ICSOC 2013, Berlin, Germany, December 2-5, 2013, Proceedings - Basu, Samik; Pautasso, Cesare; Zhang, Liang; Fu, Xiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 11th International Conference on Service-Oriented Computing, ICSOC 2012, held in Berlin, Germany, in December 2013. The 29 full papers and 27 short papers presented were carefully reviewed and selected from 205 submissions. The papers are organized in topical sections on service engineering, service operations and management; services in the cloud; and service applications and implementations.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information Systems; Management information systems; Computer Science; Software Engineering; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Management of Computing and Information Systems; Business Information Systems